PERBEDAAN BERAT BADAN BAYI ANTARA YANG DI BERIKAN ASI EKSLUSIF DENGAN YANG TIDAK PADA USIA 0-6 BULAN DI PUSKESMAS TAJINAN KABUPATEN MALANG - Sahani, Mutiara Nikita; Ilmiah, Widia Shofa; Indriati, Ina (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Breast milk is the first and best natural food for babies. Breast milk contains various nutrients needed in the process of growth and development of babies. However, until now there is still low understanding of mothers, families and society regarding the importance of breast milk for babies. The aim of this research is to find out Difference in weight of babies given exclusive breast milk and not given breast milk at the age of 0-6 months. This research design is cross sectional. The population in this study was 6 month old babies from November to December 2023 at the Tajinan Community Health Center, totaling 80 babies and 14 of them experienced weight gain that was not appropriate for their age. The sampling technique uses accidental sampling technique, data is collected by distributing questionnaires. This research uses the chi square test. Based on the research results, it can be seen that the majority of respondents who did not give exclusive breast milk had obese babies, 9 respondents (25.0%), while the majority of respondents who gave exclusive breast milk had normal weight babies, 12 respondents (33.3%). From data analysis between Exclusive Breastfeeding and Baby's Body Weight using the Chi Square Test, a significant value of p = 0.002 (p.value < 0.05) was obtained.